Effects of water, fertilizer, dissolved oxygen and temperature coupling on the photosynthesis, quality and yield of lettuce - Ouyang, Zan; Tian, Juncang (International Journal of Agricultural and Biological Engineering, 2023)
With the increased demand for vegetables of nutritional value, enhancing vegetable quality while pursuing high yield has become a goal of many investigators. In the present study, the effects of irrigation quota (A), fertilizer amount (B), dissolved oxygen (DO, C), and temperature in the climate chamber (D) applied in combination with the quality and yield of lettuce were investigated. Four-factor and three-level orthogonal designs were used to determine the single-factor trend, the sequence of primary and secondary influencing factors, and optimal regulatory measures concerning the lettuce. The order of the primary and secondary effects on the plant height, net photosynthesis rate (Pn), transpiration rate (E), vitamin C content (Vc), soluble protein content (Sp), dry matter accumulation (Dm), yield, irrigation water use efficiency (IWUE) of the lettuce plants followed the order A>B>D>C. In addition, the order of the primary and secondary effects on the intercellular carbon dioxide concentration (Ci), chlorophyll content, and nitrate content followed the order A>D>B>C. The optimum scheme for lettuce was A3B2C1D3 (irrigation quota of 69 mm; fertilizer amount of 1.30 g/pot; DO of 6.5 mg/L; and temperature in the climate chamber of 20C). Under the coordinated regulation of water, fertilizer, air, and temperature, the quality and yield of lettuce have been significantly improved. This study had important reference significance for the comprehensive regulation of water, fertilizer, air, and temperature facilities for vegetables. Keywords: aerated irrigation, increased-temperature irrigation, growth, photosynthesis, dry matter accumulation, principal component analysis DOI: 10.25165/j.ijabe.20231605.7916 Citation: Ouyang Z, Tian J C. Effects of water, fertilizer, dissolved oxygen and temperature coupling on the photosynthesis, quality and yield of lettuce. Int J Agric & Biol Eng, 2023; 16(5): 132–141.